Acts and the Praxis of Early Christian Ecumenism - Smith, David Andrew (Journal of theological interpretation, 2020)
This article is a study in practical ecumenism as expressed in the Acts of the Apostles. As the only canonical narrative to tell the story of the church, Acts has always been a key text for reflection upon ecclesial identity. Yet one feature of the ecclesiological vision of Acts, which is particularly relevant for our time, remains largely unstudied: how does Acts deal practically with difference as a characteristic of early Christian life? A surface reading of Acts, as of early Christian history generally, makes clear that ecclesial difference was a pervasive and often troubling fact of life in early Christianity. Indeed, since the time of F. C. Baur, Acts that is particularly relevant for our time remains largely understood as a rhetorical attempt to remedy a situation of ecclesial discord, though the precise divisions and troubles facing the Lukan community have been variously understood. Recent studies of Acts have rightly stressed the theological character of Luke’s vision, according to which the church’s identity and witness are fundamentally grounded in its life in Christ. Yet the practical question remains: how did such communities, separated as they were by geographic, ethnic, and theological differences, come to understand themselves as one church? This article charts the practical ecumenism according to which, in Luke’s telling, the theological identity of the church was given tangible expression, and it argues that Luke’s attention to these practices provides key data for characterizing Acts as an ecumenical document in its own right.